2011
DOI: 10.5251/abjna.2011.2.7.1087.1095
|View full text |Cite
|
Sign up to set email alerts
|

Effect of co-administration of extracts of Vernonia amygdalina and Azadirachta indica on lipid profile and oxidative stress in hepatocytes of normal and diabetic rats

Abstract: Effect of combined administration of extracts of Vernonia amydalina (VA) and Azadirachta indica (AI) on oxidative stress indices and serum lipid profile of normal and diabetic rats was evaluated. Result indicated a significant decrease (p<0.05) in catalase (CAT) activity, but non-significant decreases (p>0.05) in superoxide dismutase (SOD) and glutathione peroxidase (GPx) activities, and in the extent of lipid peroxidation non-significant increase (p>0.05) in malondialdehyde (MDA) concentration of untreated di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…It is believed that in STZ-diabetic conditions, hyperglycaemia produces ROS that exceeds endogenous antioxidant capacity; these ROS may react with polyunsaturated fatty acids of cell membranes thereby causing lipid peroxidation and membrane damage [ 35 , 36 ]. The result of the present study revealed that TBARS level in the liver of STZ-induced diabetic rats was markedly elevated when compared with the control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is believed that in STZ-diabetic conditions, hyperglycaemia produces ROS that exceeds endogenous antioxidant capacity; these ROS may react with polyunsaturated fatty acids of cell membranes thereby causing lipid peroxidation and membrane damage [ 35 , 36 ]. The result of the present study revealed that TBARS level in the liver of STZ-induced diabetic rats was markedly elevated when compared with the control.…”
Section: Discussionmentioning
confidence: 99%
“…Added to this, SOD and CAT play an essential role in attenuating cellular stress by maintaining physiological levels of oxygen and hydrogen peroxide. SOD scavenges the superoxide radical by converting it to hydrogen peroxide and molecular oxygen, while CAT brings about the reduction of hydrogen peroxides and protects higher tissues from the highly reactive hydroxyl radicals [ 35 , 41 ]. Interestingly, administration of PBPi to STZ-induced diabetic rats considerably revert the hepatic antioxidant status in a dose-dependent manner near normal when compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Pyrazinamide, in combination with isoniazid and rifampicin is also, associated with an increased incidence of hepatotoxicity [30] . In addition to these mechanisms, oxidative stress induced hepatic injury is one of the important mechanisms in hepatotoxicity produced by antitubercular drugs [31] .…”
Section: Discussionmentioning
confidence: 99%